Tic frequency and behavioural measures of cognitive control are improved in individuals with Tourette syndrome by aerobic exercise training. (August 2020) - Jackson, Georgina M.; Nixon, Elena; Jackson, Stephen R.
Abstract: Previous observations of improvements in cognition in typically developing children following moderate to vigorous exercise (e.g., Budde, Voelcker-Rehage, Pietrabyk-Kendziorra, Ribeiro, & Tidow, 2008; Hillman et al., 2009) have led to increased interest in the potential benefits of exercise for children with neurodevelopmental disorders, involving difficulties in self-regulation (e.g., Halperin & Healey, 2011; Archer & Kostrzewa, 2012). Using a within-sample design, the current study looked at the beneficial effects of non-aerobic movement training (Tai Chi), compared to aerobic movement training (Kick Boxing), on behavioural measures of cognitive control and clinical measures of tic severity in a group of young people with Tourette Syndrome (TS). We demonstrate that Kick Boxing, but not Tai Chi, led to a significant enhancement in cognitive control task performance. Furthermore, while tic frequency (tics per minute) was reduced during both types of exercise, this reduction was significantly greater, and sustained for longer, following Kick Boxing. Importantly, the magnitude of the increase in cognitive control following Kick Boxing predicted the degree of reduction in tic frequency. These findings suggest that aerobic exercise may be a useful intervention for improving self-regulation of tics in young people with TS, probably through enhancements in associated cognitive control circuits.